Osteoclastic differentiation by mononuclear phagocytes containing biomaterial particles. - Sabokbar, A; Pandey, R; Quinn, J; Athanasou, N (1998)
Aseptic loosening of implant components is a common and important complication of both cemented and uncemented prosthetic joint replacements. Wear particles derived from organic polymer and metal implant biomaterials are commonly found within macrophages and macrophage polykaryons in the fibrous membrane between loose implant components and the host bone undergoing resorption. In order to determine whether biomaterial particle-containing, foreign-body macrophages may contribute to periprosthetic bone resorption, we cultured murine monocytes that had phagocytosed particles of biomaterials commonly employed in bone implant surgery [polymethylmethacrylate (PMMA), ultra-high molecular weight polyethylene (PE), titanium and chromium-cobalt] on bone slices and glass coverslips with UMR 106 osteoblast-like stromal cells in the presence of 1,25-dihydroxy-vitamin D3. Under these conditions, all biomaterial particle-containing, foreign-body macrophages differentiated into osteoclastic cells, i.e. tartrate-resistant acid phosphatase (TRAP)-positive multinucleated cells capable of extensive lacunar bone resorption. This study shows that particle phagocytosis by macrophages does not abrogate the ability of these cells to undergo osteoclast differentiation. These findings emphasise the importance of the foreign-body macrophage response to biomaterial wear particles in the pathogenesis of aseptic loosening.